CAPAIAN INDEKS KELUARGA SEHAT PADA MASYARAKAT YANG MELAKUKAN METATAH DI DESA RAWAMANGUN, KECAMATAN SUKAMAJU, KABUPATEN LUWU UTARA: Indonesia - Amalia Ako, Elma Nugra; Muhammad Saleh; Yessy Kurniati (Andragogi Kesehatan, 2024)
The Healthy Family Index (IKS) is an index that shows family health status through 12 indicators. <The purpose of the study was to determine the achievement of the Healthy Family Index in the community who do metatah in Rawamangun Village, Sukamaju District, North Luwu Regency. The type of research used is descriptive quantitative. The population is a Hindu community with a sample size of 180 households with a sampling technique using purposive sampling. <The results showed that there were 1 household in the healthy category (0.6%), 33 households in the pre-healthy category (18.3%), and 146 households in the unhealthy category (81.2%). Most of Rawamangun Village is categorized as unhealthy households. Therefore, the researchers suggest that health workers should increase socialization related to health, especially JKN. In addition, researchers also advise local health workers to conduct counseling related to the benefits of using family planning for couples of childbearing age (PUS), as well as the dangers of smoking for health so that IKS in Rawamangun Village can increase. Keywords : Healthy Family Index (IKS), Pre-Healthy, Healthy, Unhealthy